The impact of infrastructure shocks on agricultural markets: Evidence from the Zambezi river in Mozambique - César Salazar-Espinoza; Sam Jones (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Prior to 2009, there was no direct road connection between the southern regions of Mozambique - where the capital city is located - and the more agriculturally-productive central and northern regions. In this paper, we leverage the opening of a major road bridge to identify the impact of enhanced domestic transport infrastructure on agricultural market performance. We apply a generalized difference-in-difference estimator within a dyadic regression context. While we find no reduction in the market price differential around the time the bridge opened for all treated market pairs, there is a significant and persistent price impact only among previously disconnected markets located close to the new bridge. This suggests that new infrastructure can enhance market performance, but such benefits are spatially limited.
Keywords: O13; Q13; R42; C99; 330; infrastructure; agricultural market performance; prices; natural experiment